Mechanical properties of lightweight 316L stainless steel lattice structures fabricated by selective laser melting. (5th November 2019) - Zhong, Tianlin; He, Ketai; Li, Huaixue; Yang, Lechang
Abstract: The performance of advanced and lightweight 316L stainless steel lattice structures fabricated by selective laser melting (SLM) was investigated using a range of laser energy densities (LED). A unique tetrakaidecahedron cell type was designed to construct a periodic lattice structure, which was compared with two common lattice structures of different unit cell topologies and deformation behaviors using mechanical property and quasi-static energy absorption. It was found that tetrakaidecahedron structure deserved good compressive properties and energy absorption capabilities. The fabricated strut morphology and internal porosity were investigated using confocal and scanning electron microscopy to correlate with the compressive properties of the structure. The porosity was found to increase firstly and then fluctuate smoothly with increasing LED, similar to yield strength. The yield strength and compression modulus were not independent of porosity, indicating that further improvements can be achieved by SLM process optimization. Meanwhile, nonlinear finite element analysis was used to analyze their compressive response and fracture behavior. Our results highlighted that a high performing unit cell geometry can be used for energy absorption and lightweight manufacturing applications of lattice structures. Graphical abstract: Unlabelled Image Highlights: Constructing a periodic lattice structure using a unique tetrakaidecahedron cell design. Characterization of four lattices' mechanical properties using experimental and finite element analysis validations. A lattice based on a tetrakaidecahedron unit cell provides optimum mechanical properties. Linear energy density influences the strut morphology, internal porosity and mechanical properties of the lattice structure.